Edición genética de la variedad de caña UFCP 82-1655 para inactivar el GEN BU1 y modificar la función del gen ALS mediante CRISPR/CAS9 (2019)
Genome editing is a technique used to accurately and efficiently modify the DNA within a cell. Since 2012, the CRISPR/Cas system has been used for gene editing (adding, interrupting or changing specific gene sequences) and for gene regulation in several species. For this investigation, this methodology was used to cause the functional elimination of the BU1 gene responsible for the leaf angle in sugarcane and to introduce a modification of the ALS gene to confer resistance to herbicides. To test the sugarcane gene editing system, two vectors were designed one for the BU1 gene and one for the ALS + BU1 genes, which were bombardment with a genetic gun in embryogenic calli of the UFCP 82-1655 sugarcane variety. After the bombardment, the tissue was selected with geneticin (20mg/L), the plants that survived were subjected to molecular tests using PCR, TaqMan assay and restriction enzymes. After selection with geneticin, 89 plants containing the plasmid with BU1 and 98 plants for the plasmid ALS + BU1 survived, after the molecular evaluation of these plants, the modification or insertion of the ALS gene in two plants (events ALS107 and ALS111) was found, these plants presented nucleotide T at position 653, while none of the plants turned out to be edited for the BU1 gene.